Impact of Protein Content on Proton Diffusibility in Intracranial Cysts - Goebell, E.; Fiehler, J.; Martens, T.; Hagel, C.; Forkert, N. D.; Russjan, A.; Rosenkranz, M.; Buhk, J.-H.; Groth, M.; Sedlacik, J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: The physical background of diffusion phenomena in intracranial cysts is unclear in some cases. To evaluate a potential dependency of proton diffusion on the concentration of proteins in cystic lesions we investigated the correlation of diffusion weighted imaging (DWI) and magnetization transfer ratio imaging (MTR) in intracranial cystic pathologies in vivo and in vitro with protein solutions.Materials and Methods: 21 patients (14 male/7 female) with intracranial cystic lesions underwent preoperative MRI (1.5 T) including MTR and DWI sequences. For comparison a series of samples with declining concentration of albumin was investigated in vitro with a 7 T animal scanner. Results: In the patients examination mean ADC values were 1.93 × 10−3 mm2/sec and mean MTR values were 0.2. Mean ADC value of the albumin solutions was 0.22 × 10−3 mm2/sec and mean MTR was 0.12. ADC and MTR values showed a strong negative correlation in the patients (Spearman’s rank correlation rs = –0.80, p < 0.01) and a very strong negative correlation in the in vitro examinations (rs = –1.0, p < 0.01).Conclusion: The strong negative correlation of ADC and MTR values suggest a strong influence of proteins on proton diffusion in intracranial cysts. The phenomena can be explained by macromelecules that bind nearby protons in their vicinity.
Keywords: CNS; MR-imaging; Abscess; Diffusion imaging